Penerapan model pembelajaran role playing untuk meningkatkan kemampuan pemahaman konsep siswa kelas IV sekolah dasar - Meina Nurfarida Sopandi; Hana Sakura Putu Arga; Faridillah Fahmi Nurfurqon (COLLASE (Creative of Learning Students Elementary Education), 2024)
This research has several objectives, including to find out; (1) increasing the application of the role playing learning model to students' ability to understand concepts; (2) student responses to learning using the role playing learning model; and (3) the obstacles faced by teachers in implementing learning using role playing models. The method used is a mix method with a sequential explanatory design. The research was located at Sukasari State Elementary School with research subjects of 30 class IV students. Data collection techniques through tests (pretest and posttest), observation sheets, interviews, and also questionnaires. Based on quantitative data obtained through the Ngain test, there was an increase in the ability to understand concepts in class IV students with an N-Gain score of 0.55 which was categorized as moderate. And the N-Gain Percent value is 55.7% with effective criteria. The qualitative data obtained, namely student responses, showed that the majority of students felt that the role playing model was interesting and fun, and made it easier for them to understand the material. Through interviews, the teacher revealed several obstacles, such as some students feeling less confident or reluctant to participate in role playing activities, then implementing role playing syntax requires time-consuming preparation when creating clear and interesting scenarios, and controlling the course of role playing so that it remains conducive.